Is All Discourse Official? On the Poetics of Gifting and Gossiping - Pierre-Héli Monot (European Journal of American Studies)
This essay discusses gift-giving and gossiping in a canonical American novel (John Steinbeck’s The Grapes of Wrath, 1939) by way of the two texts which sealed the fate of dominant literary scholarship after WWII: Marcel Mauss’s essay The Gift and Claude Lévi-Strauss’s Introduction to the Work of Marcel Mauss. Steinbeck’s use of informal discourse and Marcel Mauss’s descriptions of tacit compulsory reciprocation present the opportunity to dispute central assumptions in literary theory that pertain to literary meaning, interpretation, and referentiality. This essay argues that literary language is conventional precisely because its conventionality fulfills a social function; the conventional nature of literary language is in itself meaningful socially. This, in turn, suggests that the interpretation of literary texts remains dependent on a correct understanding of the material and symbolic economies they participate in.